(untitled) (Physical Education, Health and Social Sciences, 2025)
Objective: To compare the sensitivity and specificity of the platelet to lymphocyte ratio (PLR) in diagnosing neonatal sepsis when comparing it to blood culture as gold standard. Study Design: Prospective observational study. Place and Duration of Study: Department of Pediatrics, Combined Military Hospital, Sialkot from January – June 2024. Methodology: A total of 180 patients were included in the study further divided into Group-A and Group-B as culture positive and negative based on culture results sent at admission to the NICU. Platelet to lymphocyte ratio was calculated on the blood panel sent at the time of admission before starting anti-biotics. Primary variables observed were sensitivity and specificity of PLR in diagnosing early onset sepsis compared with blood culture results as gold standard. Results: The overall diagnostic parameters of PLR when compared to the gold standard blood culture results showed sensitivity of 91.7%, specificity of 91.3%, with a positive predictive value of 98.6%, negative predictive value of 61.8% with a diagnostic accuracy of 91.6%. Conclusion: We conclude that PLR provides good sensitivity and specificity of 91.7% and 91.3% with a diagnostic accuracy of 91.1% for early onset neonatal sepsis.